Pengembangan Bisnis Ikan Hias Guppy dengan Fokus Pada Kualitas Kontes (Menggunakan Analisis SWOT dan Metode Business Model Canvas) - Rovita, Angelina Levi; Herlinawati, Erna (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research aims to develop a contest quality guppy ornamental fish business using SWOT analysis and the Business Model Canvas method. The background to this research is based on the increasing public interest in ornamental fish, especially guppies, which have promising market potential. The methods used in this research include internal and external approaches through case studies to collect relevant data. The results of the SWOT analysis show the strengths, weaknesses, opportunities and threats faced in this business, while the Business Model Canvas provides a clear framework for designing an effective business model. This research found that with the right strategy, the guppy business can develop and compete in the market. The main conclusion from this research is that developing an ornamental guppy fish business requires a deep understanding of market conditions and the implementation of innovative strategies to achieve success. Thus, it is hoped that this report can make a positive contribution to the development of the ornamental fish business in Indonesia.